Pola pengelolaan pendapatan keluarga buruh tani dalam rangka memenuhi kebutuhan hidup - Feni Dwi Yulianti; Sri Umi Mintarti; Wahjoedi Wahjoedi; Yohanes Hadi Soesilo (Universitas Negeri Malang, 2021)
Abstract Income management can be identified the pattern through income and expenditure streams. This study aims to determine the pattern of income management of farm labor families in Bakung Pringgodani Village in order to meet the needs of life. This research is a qualitative research with a case study method where researchers collect data will focus on a case encountered in a family of farm workers in Bakung Pringgodani Village. The obtained data were observed and analyzed carefully to the end with the aim of understanding a phenomenon or event experienced by the family farm laborers in the village of Bakung Pringgodani. The suggestions from this study are: Farm workers' families are expected to be able to make or arrange a written financial plan so that it can facilitate the allocation of income and control expenses in order to fulfill the needs of family life. Abstrak Pengelolaan pendapatan dapat diketahui dari pola pendapatan dan pengeluaran. Penelitian ini bertujuan untuk menganalisa pola pengelolaan pendapatan pada keluarga petani untuk memenuhi kebutuhan mereka, di Desa Bakung Pringgodani. Penelitian ini merupakan penelitian kualitatif yang menggunakan metode studi kasus, dimana peneliti focus pada kasus-kasus yang dialami para keluarga petani di Desa Bakung Pringgodani. Data yang telah terkumpul diobservasi dan dianalisa untuk menjabarkan dan memahami fenomena yang dialami oleh para keluarga petani di Desa Bakung Pringgodani. Oleh karena itu, para keluarga petani disarankan untuk menyusun rencana keuangan tertulis untuk membantu pengalokasian pendapatan dan mengontrol pengeluaran dalam pemenuhan kebutuhan keluarga